2014
DOI: 10.2319/072213-533.1
|View full text |Cite
|
Sign up to set email alerts
|

Upper airway changes after Xbow appliance therapy evaluated with cone beam computed tomography

Abstract: Treatment with the Xbow appliance in Class II patients resulted in favorable increase in the oropharyngeal airway dimensions and volume. Further studies with larger study samples and with control groups are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 20 publications
3
8
0
Order By: Relevance
“…In this study, we observed no significant changes in the inferior airway space and nasopharyngeal depth. In this regard, our results are comparable with those reported by Jena et al, 18 Han et al 28 and Erbas 29 who evaluated the effects of CTB and MPA-IV, Bionator and Xbow on airway dimensions.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we observed no significant changes in the inferior airway space and nasopharyngeal depth. In this regard, our results are comparable with those reported by Jena et al, 18 Han et al 28 and Erbas 29 who evaluated the effects of CTB and MPA-IV, Bionator and Xbow on airway dimensions.…”
Section: Discussionsupporting
confidence: 91%
“…These resultsconcur with Isidor et al (24) who used monoblock and Twin-Block removable functional appliancesandreported a significant increase of 2500 mm 3 in the total pharyngeal airway. Likewise, these finding are in harmony with those of other studies (21,27) who utilized somewhat different FFAs and accomplished enhancement in the pharyngeal airway volume via CBCT. Rizk et al (21) utilized MARA appliance and reportedan increase of 2200 mm 3 while Erbas et al (27) showed increase 1700 mm 3 following X-bow Forsus appliance Although there is continuous debate regarding the effectiveness of FFAs for stimulating the mandibular growth, several reports have demonstrated successful corrections of skeletal Class II through the Herbst appliance in growing patients (2,8) .Even if there was an incremental skeletal enhancement with the rigid types of FFAs (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…The vertical anterior boundary of pharyngeal airway was represented by the line P4 which is perpendicular to FHP and tangent to PNS (Fig. 4) (24,27) . The airway volumetric analysis was performed using the "the airway analysis" module of the software.…”
Section: Pharyngeal Airway Assessmentmentioning
confidence: 99%
“…Additionally, Zhang et al [21] and Shete and Bhad [22] reported that TB appliance may improve the obstructive sleep apnea (OSA) symptoms in patients with mandibular retrognathia. Generally, the pharyngeal airway dimension changes following functional therapy were examined through two-dimensional (2D) lateral cephalograms [23][24][25] or 2D cephalometry extracted from cone beam computed tomography (CBCT) [26,27]. However, because of its 2D nature and inability to provide volumetric data, the value of lateral cephalograms is limited in the studies concerning the airway.…”
Section: Introductionmentioning
confidence: 99%